1982
DOI: 10.1093/oxfordjournals.aje.a113434
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Counts and Coronary Heart Disease in a Japanese Cohort

Abstract: Coronary heart disease incidence during 1958-1974, in a cohort of Hiroshima and Nagasaki residents, was found to relate significantly (p = 0.01) to total leukocyte count, taken an average of two years earlier. Relative risks, as a function of leukocyte count, did not appear to depend on sex or cigarette smoking status, but may be larger for subjects less than 65 years of age than for older persons. This study examines, for the first time, differential leukocyte counts and percentages in relation to coronary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
1
4

Year Published

1985
1985
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(101 citation statements)
references
References 0 publications
3
93
1
4
Order By: Relevance
“…Previous epidemiologic and clinical studies have suggested increased eosinophil count as a risk factor for coronary artery disease. [10][11][12] In addition, Erdogan et al 13 reported a significant increase in the number of eosinophils in peripheral blood in patients with unstable angina pectoris compared with that in control subjects. However, to our knowledge this is the first report to investigate the relationship between eosinophil count and CAC, which suggests new avenues for research into the pathogenesis of CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiologic and clinical studies have suggested increased eosinophil count as a risk factor for coronary artery disease. [10][11][12] In addition, Erdogan et al 13 reported a significant increase in the number of eosinophils in peripheral blood in patients with unstable angina pectoris compared with that in control subjects. However, to our knowledge this is the first report to investigate the relationship between eosinophil count and CAC, which suggests new avenues for research into the pathogenesis of CAC.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of differential leukocyte counts as a risk marker has been evaluated in a number of studies [12][13][14]. However, it is still different among studies that which type of WBC is more important.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the count is closely correlated with advanced atherosclerosis [10], and the incidence and mortality rate of CVD [11]. Various types of inflammatory cells, including monocytes, lymphocytes, eosinophils, and neutrophils, have been implicated in CHD [12][13][14]. Nevertheless, it is still different among studies that which type of WBCs is more important.…”
Section: Introductionmentioning
confidence: 99%
“…In the Hiroshima and Nagasaki Adult Health Study, 11 the total leukocyte count correlated positively with the incidence of coronary artery disease in a large population of individuals free of disease at baseline. When differential cell counts were considered, a correlation was found between a moderately elevated eosinophil count and an increased risk of disease, as well as between neutrophil, eosinophil and monocyte (but not lymphocyte) counts and the incidence of disease.…”
mentioning
confidence: 96%